PENGARUH DISIPLIN KERJA, MOTIVASI KERJA DAN FASILITAS KERJA TERHADAP KINERJA KARYAWAN PADA DINAS KETENAGAKERJAAN DI KABUPATEN SITUBONDO MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Alfadhil, Thoriq; Tulhusnah, Lusiana; Soeliha, Siti (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
The aim of this research is to analyze and test the influence of Work Discipline, Work Motivation and Work Facilities on Employee Performance at the Situbondo Regency Employment Service through Job Satisfaction as an Intervening Variable. The population in this study were employees of the Situbondo Regency Employment Service. The sampling technique is determined by Non-Probability Sampling using Total Sampling or saturated samples. Data analysis and hypothesis testing in this research used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of direct hypothesis testing using the Smart PLS 3.0 application, show that Work Discipline has a positive but not significant effect on Job Satisfaction, Work Discipline has a significant positive effect on Employee Performance, Work Motivation has a significant positive effect on Job Satisfaction, Work Motivation has a positive but not significant effect on Performance Employees, Work Facilities have a significant positive effect on Job Satisfaction, Work Facilities have a negative but not significant effect on Employee Performance, Job Satisfaction has a significant positive effect on Employee Performance. The results of the indirect effect hypothesis test show that the variable Work Discipline on Employee Performance through Job Satisfaction has a positive but not significant effect, Work Motivation on Employee Performance through Job Satisfaction has a positive but not significant effect, Work Facilities on Employee Performance through Job Satisfaction has a positive but not significant effect,